A Network Disk Device Based on Web Accessing - QunFang Yuan; Wenxia Di; YaoLi Wang (Institute of Advanced Engineering and Science, 2014)
The future personal and home demand of big data helped fuel an explosion of development in network disk device market. Compared to a traditional USB hard drive, it separated the user from the hard disk, enjoyed the advantage of accessing from anywhere for unspecific user and easy operation and easy expansion. The paper established the remote access to hard drives via browser with Xilinx's XUPV5 LX110T FPGA development board. The system mounted an ATA host controller IP core and connected it to the network with RJ45. By porting PetaLinux operating system to the MicroBlaze embedded processor of FPGA, an independent FAT32 file system module was added, the users could establish the remote access to hard drives with specific CGI programs through the WEB browser. It was tested that Personal/Home Network Disk can meet the standards of basic file operation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5472